Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values

Measuring total sustainable incomes from multifunctional management of Corsican Maritime Pine and Andalusian Cork oak Mediterranean forests - Campos, Pablo; Bonnieux, François; Caparros, Alejandro; Paoli, Jean-Christophe (Journal of Environmental Planning and Management, 2007)
Abstract Enough advances have recently been made in income accounting theory to recommend that environmental services accruing either to the forest owner or to the general public should be included in the forest accounting system. In this study, the results of two case studies, one in Bonifatu, Corsica (France) and the other in Alcornocales, Andalusia (Spain), show that private environmental services provide the majority share of social total sustainable income in Alcornocales (29%), whereas public environmental services are the most relevant in Bonifatu (32%). The social total sustainable income measured by the agroforestry accounting system is, respectively, 1.6 and 2.4 times higher than the income estimated by economic accounts for forestry in Alcornocales and Bonifatu forests.
doi: 10.1080/09640560601048424doi: 10.1080/09640560601048424The following values have no corresponding Zotero field: publisher: Routledge
Keywords: accounting system; benefits; Bonifatu; environmental services; Los Alcornocales; management (voyant); market price; sustainable income; Values